1974
DOI: 10.1073/pnas.71.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacterial Growth by β-Chloro-D-Alanine

Abstract: i3-Chloroamino acids have been shown recently to bind efficiently to transaminases and decarboxylases and to undergo #3-elimination reactions in situ (7,8). In some cases the enzyme catalyzing the (3-elimination reaction is irreversibly inactivated presumably by reaction of the enzyme-bound aminoacrylic acid with some functional group of the protein (8). Accordingly, it has occurred to us that (3-chloro-D-alanine might inhibit irreversibly the pyridoxal phosphate enzymes responsible for the formation of D-alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 20 publications
0
46
1
Order By: Relevance
“…DadA has been shown to convert D-chloroalanine to ␤-chloropyruvate, which inhibits alanine racemase activity (72,73). In addition, ␤-chloropyruvate inhibits solute transport in E. coli by a process that has not been fully characterized, but the strong alkylating properties of this molecule are believed to be responsible for this effect (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…DadA has been shown to convert D-chloroalanine to ␤-chloropyruvate, which inhibits alanine racemase activity (72,73). In addition, ␤-chloropyruvate inhibits solute transport in E. coli by a process that has not been fully characterized, but the strong alkylating properties of this molecule are believed to be responsible for this effect (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10 8 CFU of an exponentially growing CDM culture were spread on a 1.2% (wt/vol) agar plate containing a complete amino acid mixture. After plating was performed, a single crystal of the toxic peptide analog L-phenylalanyl-␤-chloro-L-alanine (FCA) (13) was put in the center of each plate. Growth inhibition was observed after 48 h of incubation at 30ЊC.…”
Section: Methodsmentioning
confidence: 99%
“…10 ) This result suggests that the metabolic enzymes of L-amino acids are inhibited by L-ACP as reported for 3-chloroalanine. 6 ) Growth inhibition of P. mirabilis in the presence of L-ACP was observed. However, the suicide inactivation of the enzyme was not observed in the a,y-elimination reaction of L-ACP.…”
Section: Identification Of the Reliction Productmentioning
confidence: 94%
“…4 ,5) Manning et al have reported that the D-and L-isomers of synthetic 3-chloroalanine inhibit the growth of Diplococcus pneumoniae, Streptococcus pyogenes, Bacillus subtilis, and Escherichia coli. 6 ) They demonstrated that the antibacterial action of 3-chloroalanine was caused by the inactivation of both n-amino acid transaminase and alanine racemase. The physiological effects of both isomers of this amino acid have been investigated and demonstrated as a suicide substrate 7 ) or an inhibitor of an active transport system.…”
mentioning
confidence: 99%